Planungskultur - fruchtbare neue Konzeption? - Fürst, Dietrich (Routledge, 2016)
Die Artikel zur wissenschaftstheoretischen Konzeption des Planungskultur-Ansatzes betrachtet den planungskulturellen Diskurs aus einer eher kritischen Perspektive und beschäftigt sich ganz grundsätzlich damit, ob Planungskultur eine fruchtbare neue Konzeption darstellt/darstellen kann und weist insbesondere auf viele methodologische Schwächen und Probleme des Ansatzes hin. Gleichzeitig hebt er aber auch dessen potenziellen Mehrwert insbesondere für international vergleichende Studien hervor, fragt aber auch kritisch, ob sich der hohe empirische Aufwand dafür lohnt.

This contribution's thrust is a critical discussion of "planning culture" approached from three aspects: (1) whether planning culture denotes a well-defined research area (doubts have been raised due to the fact that the term is quite vague and is difficult to distinguish from related concepts, such as planning style and planning governance); (2) whether the concept can be adequately handled methodologically (problematic nature of inductive theory based on case studies); (3) whether planning culture can satisfy "Ockham's Razor" (is the intention "to understand" or "to explain"? In the latter case, the concept quickly becomes overly complex, vague and undetermined - planning culture becomes a highly complex model of society).
Planning culture - a fruitful new concept?
Keywords: Planung; Theorie; Planungsprozess; Planungstheorie; Forschungsstand; Wissenschaftstheorie; Planungskultur; Konzept; Begriff; Forschungsansatz